2006
DOI: 10.1590/s0102-311x2006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Revisão sistemática sobre morbidade materna near miss

Abstract: IntroduçãoA Organização Mundial da Saúde (OMS) estima que anualmente 20 milhões de mulheres apresentam complicações agudas da gestação, com a ocorrência de 529 mil óbitos 1 . A ocorrência da morte materna extrapola a tragédia individual, constituindo um aspecto de avaliação do desenvolvimento humano 2 . Em países da África Sub-saariana, a morte materna é um evento freqüente, capaz de produzir uma razão de morte materna tão elevada quanto 1.500 óbitos por 100 mil nascidos vivos, enquanto que nos países desenvol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
4
43

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 44 publications
2
31
4
43
Order By: Relevance
“…They have focused either on clinical criteria for common diagnostic categories, management-based criteria related to specific interventions or on organ system dysfunction. [6][7][8] Previous studies have reported near-miss figures ranging from 4 to 10/1000 deliveries in high-income countries to 40 to 80/1000 deliveries in resource-poor settings. 6 So far, near-miss research has been rare in Latin America, with the exception of a recent study at a Brazilian tertiary level hospital that showed a near-miss frequency of 15 to 42/1000 deliveries.…”
Section: Introductionmentioning
confidence: 99%
“…They have focused either on clinical criteria for common diagnostic categories, management-based criteria related to specific interventions or on organ system dysfunction. [6][7][8] Previous studies have reported near-miss figures ranging from 4 to 10/1000 deliveries in high-income countries to 40 to 80/1000 deliveries in resource-poor settings. 6 So far, near-miss research has been rare in Latin America, with the exception of a recent study at a Brazilian tertiary level hospital that showed a near-miss frequency of 15 to 42/1000 deliveries.…”
Section: Introductionmentioning
confidence: 99%
“…Na avaliação inicial do desempenho do SIH-SUS, a busca nominal das mulheres identificadas A Tabela 4 traz as estimativas projetadas para os VPP e VPN do SIH-SUS na identificação do near miss materno conforme diferentes magnitudes do agravo 11 . Observa-se que, para incidên-cias variando entre 1 e 110 casos por mil nascidos vivos, o VPP variou de 0,3% a 28,7% e o VPN, de 90,4% a 99,9%.…”
Section: Critérios Clínicosunclassified
“…Ao longo dessas três décadas, o maior entrave para a efetiva consolidação do conceito de near miss materno tem sido a falta de uma demarcação teórico-operacional clara e consensual para o evento 5,6,11,12 . Frente a essa dificuldade, em 2009, um grupo de especialistas em saúde materna e perinatal propuseram, sob a chancela da OMS, que o near miss materno seja definido como "uma mulher que quase morre, porém sobrevive à complicação ocorrida na gravidez, parto ou até 42 dias após o fim da gestação" 6 (p. 289), alinhando temporalmente esta definição com a de morte materna 3 .…”
unclassified
“…This term has been used by clinical medicine, and it can be employed in several situations. In the case of obstetrics, when thinking about maternal mortality, a near miss is usually an adverse and serious event that caused harm and morbidity to the mother who, somehow, survived (4)(5) .…”
Section: Introductionmentioning
confidence: 99%